2019
DOI: 10.1017/s0376892919000110
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Fire on Forest Biomass Dynamics at the Southern Amazon Edge

Abstract: SummaryOver recent decades, biomass gains in remaining old-growth Amazonia forests have declined due to environmental change. Amazonia’s huge size and complexity makes understanding these changes, drivers, and consequences very challenging. Here, using a network of permanent monitoring plots at the Amazon–Cerrado transition, we quantify recent biomass carbon changes and explore their environmental drivers. Our study area covers 30 plots of upland and riparian forests sampled at least twice between 1996 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…Between 2007 and 2016 (the most recent survey), aboveground biomass loss (Nogueira et al, 2019), increased floristic similarity, and higher plant mortality than recruitment (da Silva et al, 2018;Maracahipes et al, 2014) were reported for the same stands included in this study ( Table 1). The most recent survey data (2014 and 2016), including trees with a diameter at breast height-DBH ≥ 10 cm in each stand, are presented in supporting information Tables S1 (species abundance), S2 (beta diversity matrix), and S3 (density, basal area, and relative basal area of trees belonging to Fabaceae).…”
Section: Site Description and Sample Collectionmentioning
confidence: 63%
See 2 more Smart Citations
“…Between 2007 and 2016 (the most recent survey), aboveground biomass loss (Nogueira et al, 2019), increased floristic similarity, and higher plant mortality than recruitment (da Silva et al, 2018;Maracahipes et al, 2014) were reported for the same stands included in this study ( Table 1). The most recent survey data (2014 and 2016), including trees with a diameter at breast height-DBH ≥ 10 cm in each stand, are presented in supporting information Tables S1 (species abundance), S2 (beta diversity matrix), and S3 (density, basal area, and relative basal area of trees belonging to Fabaceae).…”
Section: Site Description and Sample Collectionmentioning
confidence: 63%
“…Stand basal area range from 15.3 m 2 per hectare in F5 to 33.5 m 2 per hectare in F1. All these changes in the vegetation have been attributed to longer dry seasons and higher frequency of fire events by da Silva et al (), Maracahipes et al (), and Nogueira et al () but not to a particular fire event detected between 2007 (first survey year) and 2013 (last year of the fire frequency record).…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…A particular gap is the huge area of endangered forests at the transition between the Amazon and adjacent Cerrado in central Brazil. In spite of a few recent studies in eastern end of these systems [37,38] we know little about how such transition zones -potentially already on the edge climatically due to their marginal status -are faring in the changing climates of the early twenty-rst century. In the Amazon-Cerrado transition, several types of forest formations occur [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of a few recent studies in eastern end of these systems [37,38] we know little about how such transition zones -potentially already on the edge climatically due to their marginal status -are faring in the changing climates of the early twenty-rst century. In the Amazon-Cerrado transition, several types of forest formations occur [37,38]. We have been monitoring a moist tropical forest outlier in southern Mato Grosso, central Brazil, for 20 years (1996-2016) using a careful permanent plot methodology with regular reinventories of woody vegetation in a valley forest.…”
Section: Introductionmentioning
confidence: 99%